Técnicas de optimización en paneles solares: seguimiento del punto de máxima potencia solar (2015)
Abstract : Solar panels are an arrangement of several cells which convert radiation caused by the sun into electrical energy. Each photovoltaic cell has a unique optimum operating point where the product of the current by the voltage is maximum, and is referred to as maximum power point. This point changes rapidly depending on external factors such as temperature and solar radiation which causes that the maximum power point tracking or MPPT becomes an essential part of a photovoltaic system. This thesis shows a study of a photovoltaic system, which uses a boost converter and MPPT control based on Perturb and Observe algorithm or P and O. A modeling, simulation and testing of each system component is performed in order to show the main advantages and disadvantages in its application